Rapid degradation of dichloroacetonitrile by hydrated electron (eaq–) produced in vacuum ultraviolet photolysis. (October 2020) - Wu, Zihao; Shang, Chii; Wang, Ding; Zheng, Shanshan; Wang, Yuge; Fang, Jingyun
Abstract: Dichloroacetonitrile (DCAN) is one of the most toxic and common nitrogenous disinfection by-products in water treatment. It is necessary to understand how this compound can be removed. In this study, the effectiveness of vacuum ultraviolet (VUV) at 185 nm was evaluated to destroy DCAN. When water is exposed to VUV, hydroxyl radicals (HO), hydrogen atoms (H), and hydrated electrons (eaq − ) are generated. The individual contributions of these reactive species to DCAN degradation were distinguished using multiple scavengers. The results showed that eaq – was the most important species for DCAN degradation. The second-order rate constant for eaq – reacting with DCAN was calculated to be 3.16 × 10 10 M −1 s −1 using a quantitative structure-activity relationship (QSAR) method adopted from previous study, and determined to be 3.76 (±0.02) × 10 10 M −1 s −1 by competition kinetics. Although dissolved oxygen (DO) at 8 mg/L consumed 86% eaq −, the rest of eaq − still led to 93% removal of DCAN within 20 min. Chloride was the major inorganic product of DCAN degradation, while nitrate and nitrite were minor products. Quantum chemical calculation and mass balance calculation under an oxygen free condition further suggested that cleavage of C–Cl bonds was the major pathway by eaq – attack. This study demonstrated the significant role of eaq – in micropollutant destruction during VUV treatment. Graphical abstract: Image 1 Highlights: DCAN degradation mechanisms by VUV irradiation were investigated. DCAN degradation mainly relied on eaq –, rather than oxidative species. The 2 nd order rate constant of eaq – towards DCAN was determined using QSAR and competition kinetics. The role of eaq – in DCAN degradation at various DO concentrations was investigated. All of organic chlorine transformed to inorganic chlorine.